1994
DOI: 10.1287/ijoc.6.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Fast Clustering Algorithms

Abstract: This paper considers the problem of partitioning the vertices of a weighted complete graph into cliques of unbounded size and number, such that the sum of the edge weights of all cliques is maximized. The problem is known as the clique-partitioning problem and arises as a clustering problem in qualitative data analysis. A simple greedy algorithm is extended to an ejection chain heuristic leading to optimal solutions in all practical test problems known from literature. The heuristic is used to compute an initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 0 publications
0
45
0
Order By: Relevance
“…This approach to clustering was championed by Grotschel and Wakabayashi (1989) and later by Dorndorf and Pesch (1994) and Mehrotra and Trick (1998). In each case, these authors advocated the use of the edge-based model CP [Edge] and good results were reported on some small examples.…”
Section: Clique Partitioning and Clusteringmentioning
confidence: 99%
“…This approach to clustering was championed by Grotschel and Wakabayashi (1989) and later by Dorndorf and Pesch (1994) and Mehrotra and Trick (1998). In each case, these authors advocated the use of the edge-based model CP [Edge] and good results were reported on some small examples.…”
Section: Clique Partitioning and Clusteringmentioning
confidence: 99%
“…No duality gap was observed (nor a branching rule specified for the case where there would be one). A direct branch-and-bound approach is proposed in [39]. A first bound equal to the sum of negative dissimilarities is improved upon be using logical relations between the y k variables (or, in other words, exploiting consequences of the triangle inequalities).…”
Section: Branch-and-boundmentioning
confidence: 99%
“…This idea is slightly extended and studied with the name ejection chain in combination with the tabu search [26,67,74,97]. Recently, we successfully applied the variable depth search to the generalized assignment problem [137,138], which is one of the representative combinatorial optimization problems that is known to be NP-hard.…”
Section: Other Metaheuristic Algorithmsmentioning
confidence: 99%